2016
DOI: 10.1002/chem.201504524
|View full text |Cite
|
Sign up to set email alerts
|

Binary Zinc Azides

Abstract: Pure, solvent-free Zn(N ) was prepared by reaction of diethyl zinc and hydrazoic acid in aprotic solvents. The single-crystal structure determination, along with the comprehensive characterization of α-Zn(N ) and two metastable polymorphs, could be achieved for the first time. Since these data disagree in large parts with the known, previously reported values, all previous syntheses of Zn(N ) , and for comparison Zn(N ) ⋅2.5 H O and Zn(OH)N were reinvestigated, indicating that some of the earlier work has to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 29 publications
3
24
0
2
Order By: Relevance
“…Theoretical studies predict that the OCPH tautomer is significantly more stable than the HOCP and OPCH by 98.7 and 259.0 kJ mol À1 ,r espectively. [23] Thea uthors employed am ethod that has previously been used for the synthesis of HN 3 , [24] OCNH, [25] and OSNH. [21] Related studies involving mixtures of PH 3 and CO highly diluted in neon have also allowed for the determination of the microwave spectra of OCPH and OCP 13 H. [22] Thefirst evidence for the formation of OCPH by NMR spectroscopy was reported in 2016 by Hinz and Goicoechea.…”
Section: Acid-base Chemistry and The Synthesis Of Ocphmentioning
confidence: 99%
“…Theoretical studies predict that the OCPH tautomer is significantly more stable than the HOCP and OPCH by 98.7 and 259.0 kJ mol À1 ,r espectively. [23] Thea uthors employed am ethod that has previously been used for the synthesis of HN 3 , [24] OCNH, [25] and OSNH. [21] Related studies involving mixtures of PH 3 and CO highly diluted in neon have also allowed for the determination of the microwave spectra of OCPH and OCP 13 H. [22] Thefirst evidence for the formation of OCPH by NMR spectroscopy was reported in 2016 by Hinz and Goicoechea.…”
Section: Acid-base Chemistry and The Synthesis Of Ocphmentioning
confidence: 99%
“…As expected from high energy density material considerations, the decomposition of a polynitrogen compound will result in the release of a large amount of energy. [14] At the second significant decomposition step from 145 to 200 8C, an abrupt exothermic peak at about 150 8C appeared and the DSC curve suddenly rose. We concluded that the decomposition residues from the first stage exploded and much energy was released, producing an unusual DSC curve.…”
mentioning
confidence: 98%
“…More recently, improved versions have been used for the generation of HN 3 ,36 HNCO,6 and HNSO 37. A solid mixture of stearic acid and [Na(dioxane) x ]PCO ( x =1) was heated in vacuo (Scheme 2),38 thereby releasing a gas which was condensed into an NMR tube containing a solvent (toluene, dichloromethane or THF) in a bath of liquid nitrogen.…”
mentioning
confidence: 99%